Using SWOT analysis to support biodiversity and sustainable tourism in Caguanes National Park, Cuba. (1st August 2020) - Navarro-Martínez, Zenaida M.; Crespo, Christina Marie; Hernández-Fernández, Leslie; Ferro-Azcona, Hakna; González-Díaz, Silvia Patricia; McLaughlin, Richard J.
Abstract: Caguanes National Park (CNP) is one of Cuba's nine protected areas that include marine and terrestrial territory and are categorized as a National Park. It receives both domestic and international tourists who access the area by land or sea. The park's natural biodiversity has the potential to be marketed as a major draw for tourists. Flora and fauna of both terrestrial and marine environments can provide huge interest to visitors, according to their endemism, representativeness or recreational fishing interest. Additionally, exceptional speleological and cultural values characterize the area. Under the auspices of the Student Workshop on International Coastal and Marine Management (SWIMM), 18 graduate students from Cuba, Mexico, and the United States undertook a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis that focused on the area's biodiversity. Strengths and opportunities identified for CNP were rated as more important than the weaknesses and threats found. Legal designation as a protected area and the available social capital were ranked as some of the most important strengths. Some of the factors identified as weaknesses or threats may, actually, be considered as strengths or potential opportunities if they are developed and marketed effectively. Based on this analysis, the area has huge potentialities for ecotourism and educational activities. Unexpected events such as Hurricane Irma, which occurred in September 2017, will test whether CNP is a resilient system where nature and human efforts work together in the recovery. Graphical abstract: Image 1 Highlights: Biodiversity in Caguanes: richness, endemism and representativeness. Protected area designation and access to social capital ranked as strengths. Strengths and opportunities rated as more important than weaknesses and threats. Limited awareness of tourism in the park. Area has huge potentialities for ecotourism and educational activities.